Oxygen concentration effects on the burning behavior of small scale pool fires. (1st July 2019) - Chen, Jian; Zhang, Xuelin; Zhao, Yanli; Bi, Yubo; Li, Changhai; Lu, Shouxiang
Highlights: Pool fires under an oxygen concentration range of 15%–27% were conducted. Boiling burning stage becomes evidently early under high oxygen concentration. A global model was developed for burning rate enhancement rate due to oxygen. The correlation of flame height was verified under different oxygen concentration. Abstract: The paper presents an experimental study on burning behavior of small scale pool fires under different oxygen concentrations. This work is motivated by the importance of oxygen concentration effects on pool fires in special conditions where the oxygen concentration does not equal 21%, such as flight operations, industrial processes and many compartment fire conditions. Small scale pool fires burning ethanol and n-heptane are conducted in a fire propagation apparatus, where combustion with controlled oxygen concentrations could be achieved. The oxygen concentration effects on heat release rate, burning rate, boiling phenomenon and flame height are studied and discussed. Results show that the pool fire burning behavior can be divided into the following stages: initial growth, steady burning, boiling burning, and decay stages. Under high oxygen concentrations, the start time of the boiling burning stage is earlier, whereas the boiling disappears when the oxygen concentration is decreased to 15%. The heat release rate increases during the boiling stage, with more violent nuclear boiling phenomenon under high oxygen concentration. Furthermore, according to the heat transfer mechanism of pool fire, the effect of oxygen concentration on mean burning rate is discussed, where a simple but practical calculation for small scale pool fire is developed to evaluate the mean burning rate enhancement rate with oxygen concentration for different fuels. Flame appearance obviously changes with an increase in oxygen concentration. Flame height is measured and the empirical flame height correlation is verified including the effect of oxygen concentration.